Body mass index-associated responses to an ABVD-like regimen in newly-diagnosed patients with Hodgkin lymphoma - Hu, Min; Ding, Yiduo; Zhang, Haizhou; Guo, Wei; Li, Yun; Jin, Zhengming; Qu, Changju; Xia, Fan (Frontiers in Pharmacology, 2023)
The role of body mass index (BMI) in the treatment outcomes of lymphoma patients is controversial. While investigating the efficacy of ABVD-like regimen in Hodgkin lymphoma (HL) patients, we observed that obese patients had poor responses. To better understand this clinical phenomenon, we evaluated the effect of BMI on responses to ABVD-like chemotherapy in HL patients.This retrospective cohort study evaluated the clinical outcomes of all 67 patients with confirmed HL who were treated at the First Affiliated Hospital of Soochow University from November 2016 to March 2023 with an ABVD-like regimen as first-line chemotherapy. Baseline patient characteristics and clinical outcomes were compared across different BMI categories. The primary end-point was the overall response rate defined as the proportion of the HL patients who achieved complete response or partial response. The additional end-points included progression-free survival and overall survival.The median age of the HL patients was 31 years old. Of the patients, 10.4% were obese, and 17.9% patients were overweight. Interim and end-term response evaluations revealed overall response rates of 98.5% and 83.6%, respectively. The proportion of patients with potential poor prognostic factors (IPS risk factors) did not differ significantly in the responders versus non-responders. However, non-responders had a higher average BMI when compared with responders (P = 0.002). Poor overall response rates in higher BMI patients indeed manifested with shorter progression free survival (P = This is a provisional file, not the final typeset article 0.013). The minimum relative dose of the ABVD-like regimen in the overweight and obese groups was significantly lower than in the normal weight group (P < 0.001).Our analyses show that >80% of newly-diagnosed HL patients responded to the ABVDlike regimen. We find that being obese or overweight at the time of diagnosis correlated with a poorer overall response rate and that BMI was an independent risk factor in HL patients treated with the ABVD-like regimen. Lower doses of ABVD-like regimen contributed to the discrepant findings of responses in the high BMI groups. These findings indicate that newly-diagnosed, obese HL patients receiving an ABVD-like regimen require personalized treatment.